Players` physical performance in LaLiga across the season: insights for competition continuation after COVID-19 - Brito de Souza, D.; González-Garcia, J.; López-Del Campo, R.; Resta, R.; Martinez Buldú, J.; Wilk, M.; Del Coso, J. (Biology of Sport, 2021)
Due to the COVID-19 outbreak, professional football players competing in LaLiga were confined at home for ~8 weeks and then they were allowed to train to prepare the first competitive match for 4 weeks. As the duration of summer break in the prior four seasons of LaLiga (from 2015-2016 to 2018-2019) was of similar length to the suspension of the championship due to COVID-19 (~12 weeks), we have analysed the running performance of teams competing in LaLiga in these four seasons to anticipate players` physical performance after the resumption of the competition. The analysis includes the average running distance per game for each of the 38 matchdays that compose LaLiga. One-way ANOVA revealed that there was a main effect of the matchday on total running distance per match (p = 0.001), and in the distance covered between 14.0 and 20.9 km/h (p < 0.001), between 21.0 and 23.9 km/h (p < 0.001) and at above 24.0 km/h (p < 0.001). Overall, the post-hoc analysis revealed that the running patterns progressively increased during the first 8-10 matchdays and then reached a plateau which was significantly different to matchday-1 (p < 0.05). This analysis reveals that, in the prior four competitive seasons of LaLiga, players` physical performance was lower at the beginning of the season and the teams needed approximately 8-10 matchdays to reach a steady state running performance. These data suggest that football players will progressively increase their performance across the 11 matchdays remaining to complete LaLiga